Finite Size Effects In Correlated Electron Models : Exact Results. - Zvyagin, Andrei A. (World Scientific, 2005)
The book presents exact results for one-dimensional models (includingquantum spin models) of strongly correlated electrons in acomprehensive and concise manner. It incorporates important resultsrelated to magnetic and hybridization impurities in electron hosts andcontains exact original results for disordered ensembles of impuritiesin interacting systems.